The phillips curve in Italy - Rosa, Agostinho Silvestre (Economia e Desenvolvimento, 2014)
The estimation of the Phillips curve in Italy, using the wage inflation rate as a dependent variable, based on annual data from the period 1961-2012, using the Johansen Method, allows us to conclude two things. Firstly, in the long term, there are two long-term relationships: the wage inflation rate relates positively to the inflation rate, negatively to the unemployment rate and positively to the average labour productivity growth index, as was expected; the inflation rate relates positively to the wage inflation rate, negatively to the unemployment rate and positively to the average labour productivity growth index, as was expected. Secondly, in the short term, the variation of the wage inflation rate relates positively and significantly to the error correction mechanism of the first long-term relationship; therefore, there is a significant response to the equilibrium error between the wage inflation rate and its determinants (inflation rate, unemployment rate, labour productivity growth index). Besides this adjustment, the variation of wage inflation rate responds significantly and negatively to the variation in unemployment rate and significantly and positively to the average labour productivity growth.